To subtract the fractions, we need to find a common denominator. The common denominator for 2, 4, and 1 is 4.
Rewriting the given expression with a common denominator:
1/2 (z+4) - 3(1/4z+1) = 1/2 (z+4) - (3/4)(z+1)
Now, let's distribute:
= (1/2)(z) + (1/2)(4) - (3/4)(z) - (3/4)(1)
= 1/2z + 2/2 - 3/4z - 3/4
Simplifying the expression further:
= (1/2z - 3/4z) + (2/2 - 3/4)
Combining like terms:
= (2z/4 - 3z/4) + (4/4 - 3/4)
= (2z - 3z) / 4 + (1/4)
= -z/4 + 1/4
The final form of the expression is -z/4 + 1/4.
Subtract 1/2 (z+4)-3(1/4z+1) use fractions and final form
1 answer